IMPLEMENTASI KONTROL POMPA OTOMATIS PADA SISTEM DESTILASI AIR LAUT - Deni Firmansyah; Ibrahim Lammada; gina lova sari (LPPM Poltek ST Paul, 2020)
This study aims to design an automatic pump control system and assess the effectiveness of using pumps in seawater distillation systems. The system uses an Arduino Uno microcontroller for central control of all system activities and a relay as a pump switch. Ultrasonic sensors, pH sensors and TDS sensors as input to provide information on the condition of the water in the storage container, the water pump as an output for pumping and flowing sea water and distilled water. The water pump in the seawater distillation system is used to drain seawater to the initial reservoir with a water level set point >20cm, if the set point is met, the pump will turn on. The second mini pump is used to flow the distilled water to the final reservoir with a set point value of pH <8 and a TDS value <1400, so the pump will turn on. The third mini pump is used to flow distilled water to the second basin with a set point value of pH >8 and a value of TDS >1400, so the pump will turn on, therefore the use of a pump in an automatic seawater distillation system is needed and its use can be said to be effective. Keywords: Water Pump, Relay, Control